Correlation between Self Efficacy and Coping Mechanism in Patients with Type 2 Diabetes Mellitus - Umi Nadziroh; Wantiyah Wantiyah; Enggal Hadi Kurniyawan; Nur Widayati (KHD-Production, 2022)
Patients with Diabetes mellitus can experience psychological distress that is stress, depression, and anxiety. Psychological disorders in diabetic patients caused by changes in behavior in everyday life such as physical activity, regular blood glucose control, continuous drug consumption, proper diet, and avoid foot wounds. The patient's response to stress depends on positive coping mechanisms. Positive self-belief or self-efficacy of a patient to the treatment of his illness can increase positive coping mechanisms. This study aims to explain the relationship between self-efficacy with coping mechanisms in patients with type 2 diabetes mellitus. This study used correlation research design with a cross-sectional approach. Sampling technique in this study used consecutive sampling with respondents 36 outpatients type 2 diabetes mellitus in dr. Haryoto Hospital at Lumajang. Data was obtained by giving questionnaires of the Diabetes Management Self Efficacy Scale (DMSES) and the Cope Inventory, analyzed by using Spearman Rank correlation test. This study showed a significant relationship between self-efficacy and coping mechanism (p = 0.001) with a strong and positive correlation (r = 0.673) which shows the higher self-efficacy of the patient then the coping mechanism will better. Patients with type 2 diabetes mellitus who have high self-efficacy in the treatments will have good coping mechanisms in dealing with psychological distress such as stress, depression, and anxiety